Le roman d'entreprise: breaking the silence - Marks, John (Sage, 2017)
This article looks at three recent French novels novels in order to explore key themes in what has become known as the roman d’entreprise: Pierre Mari’s Résolution (2005), Nathalie Kuperman’s Nous étions des êtres vivants (2010) and Thierry Beinstingel’s Retour aux mots sauvages (2010). The figure of the entreprise functions both as a fictional representation of the post-Fordist workplace environment in companies such as France Télécom, and also as a means of tackling wider issues of work and social organisation in an era of neoliberal managerialism. The concepts of capitalist realism, organisational miasma and virtuality are used to analyse the ways in which the three novels convey the distinctive affective landscape of the contemporary entreprise. Fiction is used to consider the prolix and self-referential nature of the managerialist entreprise, which enables it to exert a significant influence on the individual and collective subjectivities of employees. The three novels focus on the capacity of the entreprise to capture language and impose an affect of silence on employees.